Digital support for female students in physical education universities in Japan - Junko Okuyama; Shuji Seto; Tomonori Motokawa; Tomomi Kato; Aya Miyamoto; Maki Maekawa; Shunichi Funakoshi; Tatsuma Okazaki; Satoru Ebihara (Scientific Reports)
Abstract Alongside acquiring specialized knowledge and accomplishing developmental tasks, athletic colleges require young athletes to also be active. We investigated the use of a smartphone application, ME-FULLNESS, as an unprecedented support method for female college students currently enrolled in athletic colleges. ME-FULLNESS is an application that infers one’s psychological state from their facial information and improves their psychological state with music, vibration, and images that match that psychological state. We conducted a psychological survey with purposively selected female university students (18 to 24 years) at the International Pacific University in Okayama, Japan, before and after one month of using ME-FULLNESS (N = 76) and a group of non-users (N = 25). The app-using group showed significant improvement in depressive symptoms (p = 0.002), anxiety symptoms (p = 0.000), stress (p = 0.000), insomnia (p = 0.002), severity of premenstrual syndrome (p = 0.000), and resilience scores (p = 0.000), while the non-app-using group showed improvement in anxiety (p = 0.009) and resilience scores (p = 0.000). This study suggests that using the ME-FULLNESS app may improve depression, stress, insomnia, and resilience among athletic female students, positively contributing to their college life and sports performance.